Exploring initial teacher education student teachers' beliefs about reflective practice using a modified reflective practice questionnaire. Issue 4 (4th July 2022) - Day, Stephen P.; Webster, Carol; Killen, Andrew
ABSTRACT: The proposition that teaching is a reflective profession is prominent within educational discourse. Theories that underpin reflection are a critical component of initial teacher education (ITE) programmes. This study aims to assess the reliability of the modified Reflective Practice Questionnaire (RPQ) in a population of ITE students; and to compare the study findings to other studies using the RPQ in other professions. This study reports cross-sectional findings for reflective capacity in ITE students undertaking three different ITE programmes, the Bachelor of Arts (Hons) (BA) Education [n=91], Professional Graduate Diploma in Education (PGDE) Primary [n=209] and Secondary [n=167], in one Scottish university. Findings show that the modified RPQ reliably assesses reflective capacity (Cronbach's alpha 0.82), which differs depending on the programme of study followed. BA students' reflective capacity is higher than that of PGDE (P) but is not different to PGDE (S) students. PGDE (P) students differing from BA students in terms of Reflection-in-Action (RiA), Self-Appraisal (SA), Confidence (general) (CG), and Confidence (communication) (CC), whereas PGDE (S) and BA students differ in terms of SA, CG CC and Stress interacting with Pupils (SiP). This study indicates student teachers' reflective capacity is higher than those found in studies of other professions.